2018
DOI: 10.1038/s41598-018-23649-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Limited Growth of Microbial Colonies

Abstract: The emergence of diffusion-limited growth (DLG) within a microbial colony on a solid substrate is studied using a combination of mathematical modelling and experiments. Using an agent-based model of the interaction between microbial cells and a diffusing nutrient, it is shown that growth directed towards a nutrient source may be used as an indicator that DLG is influencing the colony morphology. A continuous reaction–diffusion model for microbial growth is employed to identify the parameter regime in which DLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Reynolds & Fink [4] were the first to perform mat formation experiments with S. cerevisiae, and similar methods have been used in subsequent studies [5,12,21]. In these experiments, yeast cells are inoculated on semi-solid (0.3%) agar plates.…”
Section: (A) Biological Backgroundmentioning
confidence: 99%
“…Reynolds & Fink [4] were the first to perform mat formation experiments with S. cerevisiae, and similar methods have been used in subsequent studies [5,12,21]. In these experiments, yeast cells are inoculated on semi-solid (0.3%) agar plates.…”
Section: (A) Biological Backgroundmentioning
confidence: 99%
“…In both cases, TAMMiCol is able to identify the colony with a high degree of accuracy, demonstrating the versatility of the software. The statistics used here are also suitable for analysing these colonies [34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…Cross-validation analysis found that only 6 features were required to classify colonies as either smooth or fluffy. A set of three spatial indices designed specifically to quantify the growth of filamentous yeast colonies [7] have been shown to provide useful information on the morphology of yeast colonies and microbial mats [34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…To examine this notion, here we study the formation of branching patterns, which emerge in many microbes when growing on solid surfaces. Examples include bacterial species such as Pseudomonas and Bacillus (Fig 1A), fungi, slime molds, and lichen (Sumner, 2001;Ben-Jacob et al, 2004;Tero et al, 2010;Tronnolone et al, 2018). Since branching patterns in microbial colonies often emerge under nutrient-deprived conditions (Shimada et al, 2004), it is plausible that branched colony growth may represent a survival strategy for microbes.…”
Section: Introductionmentioning
confidence: 99%